Late complications of liver trauma: about 239 observations - Torterolo, Edgardo; Piacenza, Guillermo; Ríos Bruno, Guaymirán; Casanello, Guillermo; Castiglioni, Juan C; Perrier, José P; de Vecchi, Jorge; Saccone, Rodolfo (Cirugía del Uruguay, 1975)
The present work carries out a retrospective review of the secondary complications of hepatic injuries. Out of a group of 239 cases, 67 cases labelled :as severe or complex were selected: 42 blunt injuries, 20 gunshot wounds, and 5 stab wounds: Forty six ( 63 % ) were hospitalized with elements of circulatory failure and 31 of the latter ( 67 % ) were actively bleeding at the time of laparotomy. Bursting and deep fractures of the parenchyma had a very high morbi-mortality. Delayed post-operative deaths were related to bilio-hematic peritonitis, infection of sequestra or hematomas, with sepsis and acute renal failure. In these circumstances, a conservative surgical management resulted in a very high percentage of complicatlons. Resections somewhat preserved from these secondary complications. When the contuslon focus is not feasible to resect, the post-operative course must be led with aggressive criterion, in order to have early detection and treatment of eventual complications.